3D Amorphous Carbon with Controlled Porous and Disordered Structures as a High‐Rate Anode Material for Sodium‐Ion Batteries. Issue 8 (4th December 2017) - Lu, Peng; Sun, Yi; Xiang, Hongfa; Liang, Xin; Yu, Yan
Abstract: Sodium‐ion batteries (SIBs) have a promising application prospect for energy storage systems due to the abundant resource. Amorphous carbon with high electronic conductivity and high surface area is likely to be the most promising anode material for SIBs. However, the rate capability of amorphous carbon in SIBs is still a big challenge because of the sluggish kinetics of Na + ions. Herein, a three‐dimensional amorphous carbon (3DAC) with controlled porous and disordered structures is synthesized via a facile NaCl template‐assisted method. Combination of open porous structures of 3DAC, the increased disordered structures can not only facilitate the diffusion of Na + ions but also enhance the reversible capacity of Na storage. When applied as anode materials for SIBs, 3DAC exhibits excellent rate capability (66 mA h g −1 at 9.6 A g −1 ) and high reversible capacity (280 mA h g −1 at a low current density of 0.03 A g −1 ). Moreover, the controlled porous structures by the NaCl template method provide an appropriate specific surface area, which contributes to a relatively high initial Coulombic efficiency of 75%. Additionally, the high‐rate 3DAC material is prepared via a green approach originating from low‐cost pitch and NaCl template, demonstrating an appealing development of carbon anode materials for SIBs. Abstract : A 3D amorphous carbon (3DAC) with controlled porous and disordered structures is prepared via a facile NaCl template‐assisted method. As anode material for sodium‐ion batteries, 3DAC exhibits excellent rate capability (66 mA h g −1 at 9.6 A g −1 ) and high reversible capacity (280 mA h g −1 at 0.03 A g −1 ) as well as relatively high initial Coulombic efficiency of 75%.